STRATEGI GURU DALAM MENANGANI PERILAKU AGRESIF ANAK USIA DINI MELALUI PENDEKATAN BERMAIN PERAN DI TK HIFZIL ATFAL PERENDAK: STRATEGI GURU DALAM MENANGANI PERILAKU AGRESIF MELALUI BERMAIN PERAN - Ramdhan Hadi; Ida Ermiana; Darmiany (STKIP Subang, 2025)
ABSTRACT This study aims to describe teachers’ strategies in handling aggressive behavior of early childhood through a role-playing approach at TK Hifzil Atfal Perendak. Aggressive behavior in early childhood often appears in verbal forms, such as yelling, mocking, and using harsh language, as well as nonverbal forms, including hitting, kicking, pushing, and grabbing toys. This research employed a qualitative descriptive method. The research subjects consisted of three teachers. Data were collected through observation, in-depth interviews, and documentation. Data validity was ensured through source triangulation and technique triangulation, while data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that teachers implement role-playing as a strategic approach by presenting simple conflict situations, guiding children to understand emotions, and encouraging positive social interactions. The role-playing activities were conducted through several stages, including determining objectives and themes, preparing scenarios, guiding children during role enactment, providing positive reinforcement, and conducting reflection. The results show that the role-playing approach effectively reduces aggressive behavior and promotes prosocial behaviors such as empathy, cooperation, self-control, and appropriate emotional expression. These findings support Albert Bandura’s Social Learning Theory and Sara Smilansky’s Sociodramatic Play Theory, emphasizing learning through observation, imitation, and meaningful social experiences. Therefore, role-playing can be considered an effective pedagogical strategy to address aggressive behavior and enhance social-emotional development in early childhood